Solar cell nanotechnology - Tiwari, Atul.; Boukherroub, Rabah; Sharon, Maheshwar (Hoboken, New Jersey : Scrivener Publishing/Wiley, 2013)
"Focusing on the cutting-edge technologies available in the field of photovoltaics, Solar Cell Nanotechnology explores the latest research and development activities related to organic, inorganic, and hybrid materials being used in solar cell manufacturing. Several chapters are dedicated to explaining the fundamentals of photovoltaics and nanomaterials utilized in the manufacturing of solar cells. Other essential subjects, such as microcontact printing, plasmonic light trapping, outdoor and indoor efficiency, luminescent solar concentrators, and photon management in photovoltaics, are comprehensively reviewed. Written for a broad audience, this is an essential book for engineers, nanotechnologists, and materials scientists"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Solar cells -- Materials; Photovoltaic cells -- Materials; Nanostructured materials; Solar cells -- Design and construction; Photovoltaic cells -- Design and construction; TECHNOLOGY & ENGINEERING / Material Science; Nanostructured materials; Photovoltaic cells -- Design and construction; Photovoltaic cells -- Materials; Solar cells -- Design and construction; Solar cells -- Materials; Electronic books; Electronic books